New developments in melanoma: utility of ultrasound imaging (initial staging, follow-up and pre-SLNB). Issue 11 (November 2011) - Ulrich, Jens; van Akkooi, Alexander JC; Eggermont, Alexander MM; Voit, Christiane
Melanoma incidence is still increasing, but the mortality rate has remained unchanged. Lymph node metastases are the single most important prognostic factor for stage I/II melanoma patients. Currently, the standard of care with regard to the staging of these patients is the surgical sentinel node procedure. Ultrasound is not routine for the diagnostic work-up of primary melanomas. Some may use ultrasound for the preoperative assessment of the tumor thickness and lymphatic drainage, but this has not found wide application. For the follow-up of melanoma patients, ultrasound has been proven to be superior to physical examination for the detection of lymph node metastases. A meta-analysis has shown that ultrasound is superior to computed tomography (CT) and/or positron emission tomography (PET)-CT for the detection of lymph node metastases, whereas PET-CT was superior for the detection of distant visceral metastases. Ultrasound of regional lymph nodes has been incorporated into many national guidelines across Europe and in Australia for the follow-up of melanoma patients. A new avenue for ultrasound (US)-guided fine-needle aspiration cytology (FNAC) is the pre-sentinel node modality. Like the situation in breast and thyroid cancer, US-FNAC, a minimally invasive procedure, may decrease the need for surgical sentinel node staging. New ultrasound morphology criteria have significantly increased the sensitivity of this technique. Peripheral perfusion is an early sign of metastases (77% sensitivity, 52% positive-predictive value), whereas balloon-shaped lymph node was a late sign of metastases (30% sensitivity, 96% positive-predictive value). Together, these new ultrasound morphology criteria were able to accurately demonstrate metastases in 65% of sentinel node-positive patients. Future perspectives of ultrasound in melanoma include the start of a large multicenter, multicountry validation study – USE-FNAC – by the European Organisation for Research and Treatment of Cancer (EORTC) Melanoma Group. In light of new and promising adjuvant therapies, the need for ultrasound staging might increase rapidly.